The hydrological investigations on water areas of the Argentina islands archipelago: problems and prospects - Yu. V. Artamonov (Ukrainian Antarctic Journal, 2013)
In work the spatial distribution of hydrological measurement’s data carried out on water area of Argentina islands archipelago in 2001-2013 is analyzed. The procedure of carrying out of measurements is discussed and the basic difficulties arising by production of hydrological works are marked. Paths of optimization of the experimental researches, answering to the modern problems of the oceanographic direction within the framework of the State Program of Ukraine researches in Antarctica are offered.